Twenty Years of Ozone Decline Proceedings of the Symposium for the 20th Anniversary of the Montreal Protocol - Zerefos, Christos; Contopoulos, G.; Skalkeas, Gregory (Springer Netherlands : Imprint: Springer, 2009)
This book includes articles presented by leading scientists in the ozone field at the Symposium for the 20th Anniversary of the Montreal Protocol, jointly organized by the United Nations Environment Programme (UNEP), the International Ozone Commission (IO3C), the Academy of Athens and the Mariolopoulos-Kanaginis Foundation, held in Athens in September 2007. His Excellency Ban Ki-moon, the Secretary-General of the United Nations, recently stated: "The success of the Montreal Protocol shows us that there are global instruments that can help curb the impact of human activities on the global environment. We should draw lessons from this experience, and strive to replicate it." This book responds by including the history, science and lessons learned by the application of the Montreal Protocol over the past twenty years. Expressed views come from three Nobel laureates, sixty scientists and representatives of international organizations and industry. Many interesting aspects of ongoing ozone research are also presented, including comparisons of what has been achieved versus what would have been the state of ozone, climate and UV in the environment if the Protocol had never been in use.